2013
DOI: 10.1177/2048872613483588
|View full text |Cite
|
Sign up to set email alerts
|

Serum corin is reduced and predicts adverse outcome in non-ST-elevation acute coronary syndrome

Abstract: Patients with non-ST-elevation ACS have lower serum corin levels than controls. Corin levels are lower in ACS patients who later experience MACE and thus might be predictor for MACE. This new putative biomarker may be useful, either alone or in combination with other biomarkers, for cardiovascular risk stratification assessment and outcome prediction in ACS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 33 publications
4
36
0
Order By: Relevance
“…The range of serum corin (373.4-2833.3 pg/mL) detected in nonhypertensive individuals in our controls was similar to that (296-2590 pg/mL) in the previous report. 13 Recently, some small sampled case-control studies have examined circulating soluble corin in some disease states, such as heart failure, 8 acute coronary syndrome, 9 osteoporosis, 17 and pregnant hypertension. 18 Corin concentration in the circulation was decreased in heart failure 8 and acute coronary syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The range of serum corin (373.4-2833.3 pg/mL) detected in nonhypertensive individuals in our controls was similar to that (296-2590 pg/mL) in the previous report. 13 Recently, some small sampled case-control studies have examined circulating soluble corin in some disease states, such as heart failure, 8 acute coronary syndrome, 9 osteoporosis, 17 and pregnant hypertension. 18 Corin concentration in the circulation was decreased in heart failure 8 and acute coronary syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…18 Corin concentration in the circulation was decreased in heart failure 8 and acute coronary syndrome. 9 Given the connections between cardiac dysfunction and stroke, circulating corin is a candidate marker of stroke risk. However, to date, the association between circulating corin and stroke has not yet been studied in humans.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Circulating corin could be measured by enzyme-linked immunosorbent (ELISA) assays [6,[8][9][10]. To date, some small sampled case-control studies have examined circulating soluble coirn and found that corin in the circulation was decreased in osteoporosis [11], acute coronary syndrome [12], and heart failure [12] but increased in pregnant hypertension [13]. In addition, we previously found a significant and positive association of serum soluble corin with hypertension [14], obesity [15], hyperglycemia, and dyslipidemia (unpublished data) in a population of China.…”
Section: Case Reportmentioning
confidence: 99%